Um olhar sobre as caricaturas de Belmonte (1923-1927) - Gorberg, Marissa (2018)
In the 1920s, amidst the growth of megacities and the proliferation of media and their audience,artist-intellectuals introduced new forms of expression in tune with this emerging modernity.During that period, Belmonte—a cartoonist, illustrator, chronicler, historian, poet, and painter fromSao Paulo—published in the Rio de Janeiro magazines Careta and Frou-Frou a collection ofcartoons that expressively depicted the daily life of the urban elites in both public and privatesettings. Belmonte applied an ironic and satirical lens to archetypes of gender, fashion, and socialnorms, as well as encounters in a myriad of domains to highlight the complexities and tensions thatpermeated the relations of that social group.The objective of this work is to provide a reading of these cartoons, simultaneously as source andobject, as expressions of our peripheral modernity. We utilize the concept of representationtogether with analytical techniques from cultural history as methodological tools, aiming to mapideas, values, and practices of that time period. The cartoons reveal themselves as a starting pointfor reflection about a way of life that finds much resonance with the present day, twistingconventions, aspirations and the genealogy of several behaviors.